Thoughts on the management of myalgic encephalomyelitis - Jenkins, Michael (British Homeopathic Journal, 1989)
For the past few years an increasing number of patients have been presenting with ‘symptoms suggestive of myalgic encephalomyelitis’ (?ME). A very active and vociferous support group has been formed. Controversy about the nature of the illness has raged in the medical profession since the Royal Free disease outbreak in the 1950s.